Some effects of ultraviolet radiation and climate on the reproduction of Calanus finmarchicus (Copepoda) and year class formation in Arcto-Norwegian cod (Gadus morhua) - Skreslet, Stig; Borja, Angel; Bugliaro, Luca; Hansen, Georg; Meerkötter, Ralf; Olsen, Ketil; Verdebout, Jean (ICES journal of marine science, 2005)
Zooplankton sampling in 1997 identified the frontal zone of the Norwegian Coastal Current as a reproduction habitat for Calanus finmarchicus in June–August. This area is subject to considerable ultraviolet radiation (UVR), as calculated from satellite observations of ozone and cloudiness. While in situ experiments indicated UVR-induced mortality in reproducing C. finmarchicus, monthly UVR doses during the actual reproduction period did not appear to affect the abundance of the resulting generation of adolescent copepodites (CIV-V) that accumulated in a fjord habitat during October 1983–2000. Local UVR in the spawning grounds of Arcto-Norwegian cod at the Lofoten Islands in March–May was positively correlated with the stock's 0-group index, which resulted in the rejection of the hypothesis that local UVR leads to high mortality of cod eggs or reduces the abundance of prey for cod larvae. Rather, the result suggests an indirect positive effect of UVR on the survival of cod eggs and larvae, possibly by controlling harmful microbes.